Mu‐opioid receptor A118G polymorphism in healthy volunteers affects hypothalamic–pituitary–adrenal axis adrenocorticotropic hormone stress response to metyrapone. (20th April 2011) - Ducat, Elizabeth; Ray, Brenda; Bart, Gavin; Umemura, Yoshie; Varon, Jack; Ho, Ann; Kreek, Mary Jeanne
ABSTRACT The mu‐opioid receptor encoded by the gene OPRM1 plays a primary role in opiate, alcohol, cocaine and nicotine addiction. Studies using opioid antagonists demonstrate that the mu‐opioid receptor (MOP‐r) also mediates the hypothalamic–pituitary–adrenal (HPA) axis stress response. A common polymorphism in exon one of the MOP‐r gene, A118G, has been shown to significantly alter receptor function and MOP‐r gene expression; therefore, this variant likely affects HPA‐axis responsivity. In the current study, we have investigated whether the presence of the 118AG variant genotype affects HPA axis responsivity to the stressor metyrapone, which transiently blocks glucocorticoid production in the adrenal cortex. Forty‐eight normal and healthy volunteers (32 men, 16 women) were studied, among whom nine men and seven women had the 118AG genotype. The 118G allele blunted the adrenocorticotropic hormone (ACTH) response to metyrapone. Although there was no difference in basal levels of ACTH, subjects with the 118AG genotype had a more modest rise and resultant significantly lower ACTH levels than those with the prototype 118AA at the 8‐hour time point (P < 0.02). We found no significant difference between genders. These findings suggest a relatively greater tonic inhibition at hypothalamic–pituitary sites through the mu‐opioid receptor and relatively less cyclical glucocorticoid inhibition in subjects with the 118G allele.